1981
DOI: 10.1128/jb.146.2.467-475.1981
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alanine ester substitution and other structural features of lipoteichoic acids on their inhibitory activity against autolysins of Staphylococcus aureus

Abstract: Native substitution with the D-alanine ester of lipoteichoic acids (LTAs) affects their immunological properties, the capacity to bind divalent cations, and LTA carrier activity. In this study we tested the influence of the D-alanine ester on anti-autolytic activity, using extracellular autolysin from Staphylococcus aureus and nine LTAs with alanine/phosphorus molar ratios of between 0.23 and 0.71. The inhibitory activity, highest with alanine-free LTA, exponentially decreased with increasing alanine content, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(39 citation statements)
references
References 35 publications
0
39
0
Order By: Relevance
“…Lipoteichoic acids directly modulate the activity of many autolysins -repressing some and activating others (Fischer et al, 1981;Bierbaum and Sahl, 1987;Smith et al, 2000;Fedtke et al, 2007). Auto activity may also directly be regulated by LTA.…”
Section: Role Of the Gw Domainsmentioning
confidence: 99%
“…Lipoteichoic acids directly modulate the activity of many autolysins -repressing some and activating others (Fischer et al, 1981;Bierbaum and Sahl, 1987;Smith et al, 2000;Fedtke et al, 2007). Auto activity may also directly be regulated by LTA.…”
Section: Role Of the Gw Domainsmentioning
confidence: 99%
“…Nevertheless, LTA derived from Streptococcus mutans but neither deacylated LTA nor teichoic acid, inhibited polycation‐induced bacteriolysis by acting directly on the muramidases (46). The inhibitory effect of LTA on the autolysins was found to reside in a sequence of glycerophosphate units, and it was deduced that the negative charges of appropriately spaced phosphodiester groups could play a crucial role in its inhibitory effect (45).…”
Section: Lta and Phospholipids May Deregulate The Autolytic Systemsmentioning
confidence: 99%
“…How then can the synergism among microbial and host‐derived agonists be controlled at the bedside? (1–3, 13–55, 23, 105).…”
Section: Possible Therapeutic Strategiesmentioning
confidence: 99%
“…U waŝ hypothesized that the observed increase in chain length could be caused by increased celJ-to-cell adhesion or the re-"loval of a fector that promotes dechaining. Other studies have indicated that wall components such as lipoteichoic acids may also play a role in cell division and separation (3,7,9,17).…”
mentioning
confidence: 99%